‘News from home’ de Chantal Akerman: el documental autobiográfico en el contexto del documental contemporáneo - Ddo. Pablo MORENO RUÍZ,Dra. Mar MARCOS MOLANO (Fonseca, Journal of Communication, 2023)
This research focuses on Chantal Akerman’s documentary ‘News from Home’ (1977), as an example of an autobio-graphical documentary made by women. The filmmaker’s story goes through the foundations of the filial maternal relationship to provoke a reflection on the relationship between women, the generational pulse, the day-to-day routine or the extraordinary nature of their lives, the emotional void